2022-RA-1461-ESGO Nectin4 as a novel prognostic marker for endometrial carcinoma. (20th October 2022) - Choi, Jung-A; Chung, Joon-Yong; Kim, Hyosun; Cho, Hanbyoul; Kim, Jae-Hoon
Abstract : Introduction/Background: The adhesion molecule Nectin-4 represents a new potential therapeutic target in different cancer models, but there has been little exploration of its diagnosis significance in endometrial cancer (EC). Methodology: EC samples from 258 patients were analyzed for Nectin4 by IHC on TMAs. Clinical outcomes were analyzed and stratified by MSH2, MSH6, MSI, and p53 with Nectin4. Progression-free (PFS) and overall survival (OS) were estimated using Kaplan-Meier methods via Cox proportional hazards regression. We generated the ROC curves to determine the optimal cutoff values of Nectin4 levels for the prediction of EC. Results: We found that Nectin4 was overexpressed strongly in archival tumor tissues from 258 EC patients than those healthy control and EIN by immunohistochemical staining. We showed that Nectin4 expression is associated with high grade and the impaired expression of DNA mismatch repair (MMR gene; MSH2, MSH6) and p53, while there was no association between other clinical parameters and risk factors. Among them, patients with high Nectin4 expression in MSH2-deficiency EC exhibited a short PFS than those with low Nectin4 expression. Furthermore, our ROC analysis showed that EC could be distinguished from healthy control according to the Nectin4 levels, with an AUC value of 0.887 [95% CI, 0.852–0.916] with higher specificity [94.25%] and PPV [98.2%]. Of note, our bioinformatics analysis of public data revealed the gene alteration of Nectin-4 in EC [14%], and its expression is well associated with gene alteration and expression of ERRB2 [spear's correlation.=0.203, p<0.0001] and ERRB3 [spear's correlation.=0.381, p<0.0001]. Conclusion: Our results indicate that Nectin4 is a novel diagnostic marker for EC, and their high expression in MSH2 deficient EC predicts a worse outcome of disease-free survival. These results may provide clues in identifying EC patients for adjuvant therapy.